Optimizing COD removal, lignin degradation and electricity generation from pulp and paper industry wastewater by CW-MFC using box-behnken design - Narayan, Maitreyie; Solanki, Praveen; Srivastava, Rajeev Kumar; Mittal, Amit; Singh, Nandan; Akhter, Fareeda; Siddiqui, Sazada (Frontiers in Energy Research, 2025)
The novel and distinctive microbial fuel cell coupled with a built wetland (CW-MFC) is a technology that treats different kinds of wastewater and produces electricity. In comparison to traditional MFCs, it is also easier to maintain and has better wastewater treatment efficiency. This study looked into the impact of wetland plants and hydraulic residence time (HRT) on treatment and energy production. There was also investigation into the features of wastewater deterioration. The lignin-degrading microcosm uses immobilized peroxidase enzyme that has been synthesized on sodium alginate beads. Using the Response Surface Methodology model, for optimization of lignin degradation, power production, and COD removal by peroxidase enzyme was mathematically investigated. Following optimization, the highest treatment given to the wastewater was 74.99%, 3.08 days of HRT, and 10 mg/L for peroxidase concentration andthe results we got were: lignin degradation was 751.1 mg/L, voltage generation was 32.09 mV and COD removal was 245.07 mg/L. The desirability of model was 0.809.